Changes in left ventricular systolic function after transcatheter patent ductus arteriosus closure in premature infants - Aravinth Karunanandaa; Joseph Paolillo; Amanda Cook; Kamala Swayampakala; Matthew C Schwartz (Wolters Kluwer Medknow Publications, 2023)
Background : Changes in left ventricular (LV) systolic function have not been well described in premature neonates after transcatheter patent ductus arteriosus (PDA) closure. Methods and Results : We retrospectively identified all premature neonates < 3 kg who underwent a transcatheter PDA closure at our center between January 1 2015 and January 31, 2021. LV indices before and after closure were extracted and an analysis was performed. Overall, 23 neonates were included with a mean procedural weight of 1894 ± 622 g. At 24 h after closure, the median left ventricular ejection fraction (LVEF) (66% interquartile range [IQR] 12% vs. 61% IQR 12, P< 0.001) and median LV end-diastolic dimension z-score (3.3 IQR 1.8 vs. 1.4 IQR 2.6, P < 0.001) both decreased and 5 (22%) neonates had an LVEF <55%. Patients who had an LVEF <55% at 24 h had a higher preprocedure LV end-diastolic dimension z-score (4.2 IQR 1.2 vs. 2.8 IQR 1.6, P = 0.01), a higher preprocedure LV end-diastolic volume (19 mL IQR 4 mL vs. 11 mL IQR 11, P = 0.03), a higher birth weight (940 g IQR 100 g vs. 760 g IQR 140, P = 0.04), and were more likely to receive intravenous calcium during the procedure (60% vs. 11%, P = 0.04) compared to those with an LVEF ≥55% at 24 h after closure. Of those with LVEF <55% at 24 h, all normalized before discharge. Conclusion : In preterm neonates who underwent successful transcatheter PDA closure, 23% developed abnormal LVEF after closure and those with significant LV dilation before the procedure were at increased risk for the development of LVEF <55% after closure.